Analysis and Synthesis of Discrete-Time Interconnected Positive Systems. Issue 2 (1st March 2018) - Ichihara, Hiroyuki; Tanabe, Shoya; Ebihara, Yoshio; Peaucelle, Dimitri
Abstract : This paper presents analysis and synthesis of interconnected systems where the interconnected system of interest consists of discrete-time positive subsystems and an interconnection matrix. The paper gives sufficient conditions for the discrete-time single-input single-output (SISO) subsystems and the interconnection matrix so that the interconnected system has the property of persistence. The fundamental differences for the persistence between the conditions of the discrete-time setting and those of a continuous-time setting are also discussed. The obtained analysis result can apply to formation control for multi-agent systems, which is a synthesis part of the paper. Numerical examples including formation control of mobile robots are shown to illustrate the proposed formation control design method.